2016
DOI: 10.1016/j.eats.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Trochanteric Bursectomy and Iliotibial Band Release for Persistent Trochanteric Bursitis

Abstract: Lateral hip pain associated with trochanteric bursitis is a common orthopedic condition, and can be debilitating in chronic or recalcitrant situations. Conservative management is the most common initial treatment and often results in resolution of symptoms and improved patient outcomes. These modalities include rest, activity modification, physical therapy, anti-inflammatory medication, or corticosteroid injections. However, there is a subset of patients in which symptoms persist despite exhaustive conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…This is followed by shaver resection of the resulting flaps to create an ellipsoid or diamond-shaped defect, followed by a thorough endoscopic bursectomy. 7,8 Similar to the findings of the aforementioned study on iliopsoas release, I have found that I tend to perform concurrent ITB release during hip arthroscopy less and less over time. Unmistakably, lateral hip pain is a common problem in patients with FAI, but it is important to identify which patients develop this pain as a result of compensation due to their intra-articular pathology versus which patients have developed a separate pathology that won't necessarily improve with hip arthroscopy alone.…”
Section: See Related Article On Page 1845supporting
confidence: 71%
“…This is followed by shaver resection of the resulting flaps to create an ellipsoid or diamond-shaped defect, followed by a thorough endoscopic bursectomy. 7,8 Similar to the findings of the aforementioned study on iliopsoas release, I have found that I tend to perform concurrent ITB release during hip arthroscopy less and less over time. Unmistakably, lateral hip pain is a common problem in patients with FAI, but it is important to identify which patients develop this pain as a result of compensation due to their intra-articular pathology versus which patients have developed a separate pathology that won't necessarily improve with hip arthroscopy alone.…”
Section: See Related Article On Page 1845supporting
confidence: 71%
“…The Abductive Strength of Operated Hip After ITB Release One of the most critical concerns of ITB release is the possibility of compromise of abductive strength. As far as we know, the cruciate incision or transversal incision technique reported in previous studies had no obvious affection on abductive force of the hip 14,20,28 . In our study, the mean abductive force of affected hips in FAI + ESH group was smaller than that in FAI group 3 months after surgery, but was similar at 2 years after surgery, indicating that ITB release during primary hip arthroscopy would delay the recovery of abductive force of the affected hip but would not have a final negative effect on it.…”
Section: Therapeutic Strategy For Fai Syndrome With Esh Using Itb Release Techniquementioning
confidence: 67%
“…The technique of ITB release is still developing and surgeons have preferred endoscopic to open surgery for ITB release in recent years. Mitchell et al 28 . reported an endoscopic ITB release technique, by performing cruciate incision on ITB, 2 cm horizontally and 2 cm longitudinally, to release the tight ITB and expose the trochanteric bursa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Z-plasty technique and the modified Z-plasty technique for lengthening the ITB, as well as endoscopic cruciate or transversal incision in the ITB for release, have been reported to have good results. [6][7][8] In another study by Maldonado et al, 9 they described a combination of a transverse incision in the ITB at the level of the tip of the greater trochanter (GT) and a longitudinal incision across the femoral insertion of the GMTda technique described by Polesello et al 10 for ESH. This technique for ITB release is more aggressive than ours.…”
Section: See Related Article On Page 1890mentioning
confidence: 99%